Dear Parents : A Field Guide for College Preparation - McGee, Jon, 1962- (Book collections on Project MUSE., 2018)
"Written for parents and families of college-bound students, this book is the one tool they'll need to navigate the complex (and often emotional) challenge of getting their daughters or sons into--and through--college. From early childhood to setting up their dorm room, this book provides parents with insights, wisdom, and guidance about college (what it is and why it is a valuable experience), college preparation (including both academic and financial), and choosing a college (how to understand not only the process but also the right fit and value). Letters written by college and educational professionals, all with their own college-aged children, frame and illuminate each chapter. The letters offer advice about preparation for college gleaned from personal and professional experiences. Undergirded by research but informed by many years of experience, Dear Parents is designed to both engage and inform parents"--